2016
DOI: 10.1002/biof.1307
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cAMP levels by high‐fat diet and curcumin and regulatory effects on CD36/FAT scavenger receptor/fatty acids transporter gene expression

Abstract: Curcumin, a polyphenol from turmeric (Curcuma longa), reduces inflammation, atherosclerosis, and obesity in several animal studies. In Ldlr mice fed a high-fat diet (HFD), curcumin reduces plasma lipid levels, therefore contributing to a lower accumulation of lipids and to reduced expression of fatty acid transport proteins (CD36/FAT, FABP4/aP2) in peritoneal macrophages. In this study, we analyzed the molecular mechanisms by which curcumin (500, 1000, 1500 mg/kg diet, for 4 months) may influence plasma and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 88 publications
(135 reference statements)
1
29
1
Order By: Relevance
“…Using Illumina sequencing and bioinformatics analysis, we identified 79, 124 and 77 DEMs (including 53, 79 and 34 conserved known miRNAs, respectively) that responded in total to HSD treatment in intestines, livers, and brains of M. amblycephala , respectively. GO classification and KEGG pathway analysis for predicted targets of the DEMs showed that these DEMs were associated with the PPAR pathway [11,12,13], the cAMP response element-binding protein [14], and the insulin signaling pathway [12,13,15], which are associated with metabolism regulation of glucose and lipid metabolic pathways and biosynthetic processes, demonstrating the important roles of these DEMs in glucose and lipid metabolisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Illumina sequencing and bioinformatics analysis, we identified 79, 124 and 77 DEMs (including 53, 79 and 34 conserved known miRNAs, respectively) that responded in total to HSD treatment in intestines, livers, and brains of M. amblycephala , respectively. GO classification and KEGG pathway analysis for predicted targets of the DEMs showed that these DEMs were associated with the PPAR pathway [11,12,13], the cAMP response element-binding protein [14], and the insulin signaling pathway [12,13,15], which are associated with metabolism regulation of glucose and lipid metabolic pathways and biosynthetic processes, demonstrating the important roles of these DEMs in glucose and lipid metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that the appropriate carbohydrate ratio in the feed of M. amblycephala is 30–34%, and higher carbohydrate feeding results in glucose intolerance responses including declined glucose metabolic enzyme activity and liver antioxidant abilities, persistent hyperglycemia, and even increased susceptibility to pathogenic bacteria [8,9,10]. For molecular illumination, excessive glucose load in M. amblycephala caused a consequence of metabolic disorders and dysfunctions in biological processes and molecular pathways in glucose and lipid metabolisms, including the peroxisome proliferator-activated receptor (PPAR) pathway [11,12,13], the cyclic adenosine monophosphate(cAMP) response element-binding protein [14], and the insulin signaling pathway [12,13,15], which associate with metabolism regulation. In addition, this dysregulation could be regulated by abnormal expression of genes and microRNAs (miRNAs, single-stranded non-coding RNA molecules length at 18–25 nucleotides) in response to those stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…CD36, a fatty acid transport protein, inhibits myocardial PKA activity and cAMP levels through tyrosine kinase-dependent mechanisms such as JNK or p38373839. CD36 is recently reported as an MMP-9 substrate27.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 4‐hydroxynonenal is increased with vitamin E deficiency and macrophage foam cells derived 4‐hydroxynonenal induces senescence in endothelial cells . As with oxLDL and a few specific lipids , CD36 is up‐regulated by 4‐hydroxynonenal involving the NRF2 transcription factor binding sites present in the CD36 promoter of mouse and humans possibly triggering senescence .…”
Section: Modulation Of Signaling Pathways By Vitamin E Relevant To Cementioning
confidence: 99%
“…Accordingly, 4-hydroxynonenal is increased with vitamin E deficiency (272) and macrophage foam cells derived 4hydroxynonenal induces senescence in endothelial cells (273). As with oxLDL and a few specific lipids (161,274), CD36 is upregulated by 4-hydroxynonenal involving the NRF2 transcription factor binding sites present in the CD36 promoter of mouse and humans possibly triggering senescence (156,275). Delaying cellular senescence in vivo by clearance of senescent cells by drugs or reducing their senescent phenotype by long-term supplementation with bioactive molecules such as vitamin E may play a role in the prevention of disease by having a positive effect on general health and health span, but an effect on lifespan remains controversial (265,268,276,277).…”
Section: Modulation Of Signaling Pathways By Vitamin E Relevant To Cementioning
confidence: 99%